2014
DOI: 10.1007/s10834-014-9395-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Saving Motives of Chinese Urban Consumers

Abstract: Prior research on the saving behavior of Chinese consumers gave indirect evidence of various saving motives. In contrast, this study examined saving motives directly reported by consumers in a national survey in China. Findings indicated that the three most commonly reported motives were saving for emergency, children's education, and retirement. Mediation analysis results suggested that saving motives reported by Chinese survey participants had clear life cycle patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…The Life-cycle theory predicts that the decisions of households about consumption and saving are based on their lifetime income, implying that household saving rates differ across different stages of the life-cycle. In line with this theory, Yao et al (2015) show that Chinese households save for different reasons at different life-cycle stages. For example, middle-aged households are more likely to save for retirement than other age groups, and younger households are more likely to save for purchasing a home or car.…”
Section: Exploring Life-cycle Effectssupporting
confidence: 66%
“…The Life-cycle theory predicts that the decisions of households about consumption and saving are based on their lifetime income, implying that household saving rates differ across different stages of the life-cycle. In line with this theory, Yao et al (2015) show that Chinese households save for different reasons at different life-cycle stages. For example, middle-aged households are more likely to save for retirement than other age groups, and younger households are more likely to save for purchasing a home or car.…”
Section: Exploring Life-cycle Effectssupporting
confidence: 66%
“…Student loan debt is unique from other forms of debts in that it is an investment in human capital and associated with a steeper earning path that would result in greater satisfaction overall (Robb, Chatterjee, Porto, & Cude, 2018). Homeownership is a major reason for families with children to have mortgage debt compared to their childless counterparts, which is similar to the situation where families with or without children have different saving motives (Yao, Xiao, & Liao, 2015). Previous research showed that debt delinquency patterns varied with family lifecycle stages that formed by age, marital status, presence of children, and age of children (Xiao & Yao, 2014).…”
Section: Debt and Family Structurementioning
confidence: 99%
“…Specific motives for saving in emerging adulthood have been largely understudied (Otto, 2009 ), especially in the period of conjuncture following the 2008 economic crisis. A few studies suggest, however, that saving for retirement becomes more prominent later in adulthood (Webley & Nyhus, 2008 ), while the precautionary motive is recognized throughout adulthood (Yao et al, 2015 ), and is also widespread among adolescents (Chudzian et al, 2015 ; Legenzova & Gaigalienė, 2017 ). Moreover, a considerable percentage of adolescents and emerging adults save money without a specific goal, as a precautionary measure or for near-term purchase of expensive goods (Otto, 2013 ; Webley & Nyhus, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%